HUBUNGAN ANTARA PENDIDIKAN DAN USIA IBU DENGAN PEMERIKSAAN PAP SMEAR DI RUMAH SAKIT PUSRI PALEMBANG TAHUN 2010 - Lili Andriani, Leny Lili Andriani, Leny (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2012)
ABSTRACT A Pap smear is an effort to capture the fluid from the vagina to see abnormalities in the cells around the cervix. Every year around the world as much as 400 thousand women are diagnosed with cervical cancer. Risk factors that can increase the chances of developing cervical cancer are age, parity, socioeconomic, education, knowledge and work. Cervical cancer is preventable as long as the symptoms are treated from the very beginning, through regular Pap smears. The purpose of this study to determine the relationship between education and maternal age with a pap smear examination at the Hospital Pusri Palembang in 2010. Design This study is a survey of analytical approaches indepeden Cross Sectional where variables (education and maternal age), and the dependent variable (Pap smear) were collected at the same time. The study population was all mothers who had conducted inspections and recorded at the Polyclinic Hospital of Gynecology Pusri Palembang period January 2010-December 2010. The sample in this study using random sampling method with Simple Random Sampling technique or simple random sampling. The results of univariate analysis of data showed the respondents who had a pap smear to check as many as 76 people (43.2%) and who never examined Pap smears as many as 100 people (56.8%). Respondents who have higher education as many as 121 people (68.8%) and who have lower education as many as 55 people (31.3%), and respondents who have a high risk age as many as 140 people (79.5%) and who have age as many as 36 people at low risk (20.5%). From the results of Chi-Square test found no significant relationship between education with Pap smears, where p value = 0.040 is smaller than α = 0.05, and there was a significant association between maternal age with a pap smear, where p value = 0.001 is smaller than α = 0.05. Based on the results of the study researchers suggest that further improve services and health education, especially regarding Pap smears to the community ABSTRAK Pap smear adalah upaya pengambilan cairan dari vagina untuk melihat kelainan sel di sekitar leher rahim. Setiap tahun diseluruh dunia sebanyak 400 ribu perempuan didiagnosa menderita kanker serviks. Faktor resiko yang dapat meningkatkan peluang berkembangnya kanker serviks yaitu usia, paritas, sosial ekonomi, pendidikan, pengetahuan dan pekerjaan. Kanker serviks memang bisa dicegah asalkan gejalanya ditangani sejak sangat awal, melalui pemeriksaan pap smear secara teratur. Tujuan penelitian ini untuk mengetahui hubungan antara pendidikan dan usia ibu dengan pemeriksaan pap smear di Rumah Sakit Pusri Palembang tahun 2010. Desain Penelitian ini adalah survei analitik dengan pendekatan Cross Sectional dimana variabel indepeden (pendidikan dan usia ibu), dan variabel dependen (Pap Smear) dikumpulkan dalam waktu yang bersamaan. Populasi penelitian ini adalah seluruh ibu yang pernah melakukan pemeriksaan dan tercatat di Poliklinik Ginekologi Rumah Sakit Pusri Palembang periode Januari 2010-Desember 2010. Sampel pada penelitian ini menggunakan metode random sampling dengan teknik Simple Random Sampling atau pengambilan sampel secara acak sederhana. Hasil analisis univariat data menunjukkan responden yang pernah memeriksakan pap smear sebanyak 76 orang (43,2%) dan yang tidak pernah memeriksakan pap smear sebanyak 100 orang (56,8%). Responden yang memiliki pendidikan lebih tinggi sebanyak 121 orang (68,8%) dan yang memiliki pendidikan lebih rendah sebanyak 55 orang (31,3%), dan responden yang mempunyai usia resiko tinggi sebanyak 140 orang (79,5%) dan yang memiliki usia beresiko rendah sebanyak 36 orang (20,5%).Dari hasil uji Chi-Square didapatkan ada hubungan yang bermakna antara pendidikan dengan pemeriksaan pap smear, dimana p value = 0,040 lebih kecil dari α = 0,05, dan ada hubungan yang bermakna antara usia ibu dengan pemeriksaan pap smear, dimana p value = 0,001 lebih kecil dari α = 0,05. Berdasarkan hasil penelitian peneliti menyarankan agar lebih meningkatkan pelayanan dan penyuluhan kesehatan terutama tentang pemeriksaan pap smear kepada masyarakat.